2014
DOI: 10.1002/jrs.4500
|View full text |Cite
|
Sign up to set email alerts
|

Pigment identification of an illuminated mediaeval manuscriptDe Civitate Deiby means of a portable Raman equipment

Abstract: Direct identification of pigments in mediaeval illuminated manuscripts was one of the first applications of Raman spectroscopy in art and archaeology. In previous in situ analysis of handwritings, the equipment was typically provided with a single excitation source. In this work, a portable Raman spectrometer (EZRAMAN-I-DUAL Raman system) is introduced to characterise the pigments used in an important illuminated mediaeval manuscript, De Civitate Dei (Library in Bruges, Ms.106). Characteristics important for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…The purpose of this work is to describe possible difficulties that are encountered during in situ Raman measurement of Patagonian prehistoric rock art, and some possible improvements are suggested. The portable Raman spectrometer used in this project was also applied in previous studies, covering a broad range of artefacts, such as the analysis of a mediaeval wall painting, glass glyptics, illuminated mediaeval manuscripts, 16th century majolica tiles, the ‘Mad Meg’ oil painting by Pieter Bruegel the Elder and identification of different minerals . Its application for the direct analysis of rock art paintings from Patagonia, Argentina, is described and discussed for the first time in this paper.…”
Section: Resultsmentioning
confidence: 99%
“…The purpose of this work is to describe possible difficulties that are encountered during in situ Raman measurement of Patagonian prehistoric rock art, and some possible improvements are suggested. The portable Raman spectrometer used in this project was also applied in previous studies, covering a broad range of artefacts, such as the analysis of a mediaeval wall painting, glass glyptics, illuminated mediaeval manuscripts, 16th century majolica tiles, the ‘Mad Meg’ oil painting by Pieter Bruegel the Elder and identification of different minerals . Its application for the direct analysis of rock art paintings from Patagonia, Argentina, is described and discussed for the first time in this paper.…”
Section: Resultsmentioning
confidence: 99%
“…The Nastova's group in Macedonia investigated medieval old‐Slavonic, Byzantine and post‐Byzantine manuscripts and Islamic illuminated manuscripts (16–18th century), where a rich palette was identified: vermilion, red lead, lazurite, realgar/pararealgar, orpiment, malachite and its degradation products, atacamite and brochantite. In the illuminated mediaeval manuscript De Civitate Dei, Lauwers et al identified mosaic gold (i.e. tin(IV) sulphide SnS 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…3 The use of mobile Raman instrumentation in archaeometry was recently reviewed. 3,21 For the in situ analysis of medieval manuscripts, mobile instruments were brought into a library 22 or museum, 23 where the analyses took place. Often these investigations took place in a separate dark room where there was little interference from ambient light.…”
Section: Spectroscopic Analysismentioning
confidence: 99%